2018
DOI: 10.1177/1941738118795425
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Low Back Pain in Golfers: A Systematic Review and Meta-analysis

Abstract: Individual demographic and anthropometric characteristics may be associated with low back pain, but this does not support a relationship between swing characteristics and the development of golf-related pain. Additional high-quality prospective studies are needed to clarify risk factors for back pain in golfers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…al. [18]. We also found that nurses with a bachelor's de-gree or above had a 0.60-fold higher risk of developing NSCLBP than nurses with a specialist degree or less.…”
Section: Characteristics Of Included Studies and Publication Biassupporting
confidence: 53%
“…al. [18]. We also found that nurses with a bachelor's de-gree or above had a 0.60-fold higher risk of developing NSCLBP than nurses with a specialist degree or less.…”
Section: Characteristics Of Included Studies and Publication Biassupporting
confidence: 53%
“…[5,6] Many factors are reported to contribute to the LBP, such as nerves, bones, musculatures, fascia, joints, and any other conditions that may result in this disorder. [710] If this condition cannot be treated effectively, it may result in very poor quality of life in patients who experienced LBP. [1113]…”
Section: Introductionmentioning
confidence: 99%
“…Our SR confirmed, also for running, the findings of a recent SR [33] which concluded that the evidence about prevalence of LBP in athletes of some popular sports are scarce and derived from studies not of good methodological quality. This SR showed a quite high LBP prevalence among athletes, but this finding was relative to a wider sample of sports including volleyball, track and fields, swimming, golf, ski, gymnastics and rowing [33,[43][44][45][46][47][48], not specifically including running.…”
Section: Consistencymentioning
confidence: 63%
“…As seen in the general population, a big amount of athletes also experiences LBP [41][42][43][44][45][46][47][48]. Moreover, athletes of particular sport disciplines such as ski, rowing, golf, volleyball, track and fields, swimming or gymnastics are at greater risk of suffering from LBP than nonathletes population [33,41,[43][44][45][46][47][48]. The incidence rates of low back pain in athletes have been reported up to 30% depending on the specific sport they are involved in [49].…”
Section: Introductionmentioning
confidence: 99%